2021
DOI: 10.12968/bjon.2021.30.5.s21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance and quality of life impact of an absorbent bacteria-binding foam dressing

Abstract: The aim of this prospective multicentre observational study was to assess the clinical performance and safety of Cutimed® Siltec® Sorbact® absorbent bacteria-binding foam dressing in wound healing and its impact on patients' quality of life (QoL). The study was conducted under routine clinical conditions in 5 study sites in Germany and Poland. Each patient with a venous leg ulcer (VLU) or a diabetic foot ulcer (DFU) was observed for 28 days (initial visit and close-out visit, as well as 3 control visits). An a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In a previous prospec ve observa onal study on pa ents with venous leg ulcers and diabe c foot ulcers assessing the clinical performance, safety and pa ent quality of life, clinicians rated the following assessment parameters in rela on to the dressings as 'very good' to 'good': wearing comfort (rated by the pa ent), applica on and removal, exudate absorp on with or without compression and fluid reten on capacity with or without compression and infec on management. 52 Pa ent comfort, when assessed in a series of 25 orthopedic and traumatology pa ents with wounds treated on a surgical ward, DACC-coated dressing was also found good outcome with regard to pa ent comfort (as assessed by parameters including pain experienced). 28 Pa ent comfort was assessed through the frequency of wound care performed on the pa ent over the course of the assessment and an assessment of pain experienced at each wound care event (e.g., dressing change).…”
Section: Pa Ent Comfortmentioning
confidence: 90%
“…In a previous prospec ve observa onal study on pa ents with venous leg ulcers and diabe c foot ulcers assessing the clinical performance, safety and pa ent quality of life, clinicians rated the following assessment parameters in rela on to the dressings as 'very good' to 'good': wearing comfort (rated by the pa ent), applica on and removal, exudate absorp on with or without compression and fluid reten on capacity with or without compression and infec on management. 52 Pa ent comfort, when assessed in a series of 25 orthopedic and traumatology pa ents with wounds treated on a surgical ward, DACC-coated dressing was also found good outcome with regard to pa ent comfort (as assessed by parameters including pain experienced). 28 Pa ent comfort was assessed through the frequency of wound care performed on the pa ent over the course of the assessment and an assessment of pain experienced at each wound care event (e.g., dressing change).…”
Section: Pa Ent Comfortmentioning
confidence: 90%
“…Several studies examined the role of foam dressings in patients with leg ulcers and PUs and reported positive outcomes with regard to no pain being experienced whilst the dressing was in situ or at dressing change/ removal. 143,115,113,144 The case series examining the use of crushed oral prednisolone tablet mixed with Stomahesive Protective Powder for the management of pain associated with peristomal pyoderma gangrenosum 145 presents a novel use of a medication to treat a relatively rare presentation*.…”
Section: Procedural-related Pain: Role Of Dressingsmentioning
confidence: 99%
“…The ability of DACC wound dressings (eg, gel) to reduce pain in a short time until it is abolished makes it a key element in the therapy and prevention of complex pediatric lesions. 72 Scalp defects, including occipital (posterior skull region) wounds, can be a particularly difficult problem, 73 particularly in terms of the congenital malformations that are due to structural anomalies of the craniofacial complex. As with adults, pediatric patients are at risk for pressure ulcers 74 with the occipital region at increased risk in infants and children compared to adults.…”
mentioning
confidence: 99%